Is high myopia a risk factor for visual field progression or disk hemorrhage in primary open-angle glaucoma? - Nitta K (Dove Medical Press, 2017)
Koji Nitta,1 Kazuhisa Sugiyama,2 Ryotaro Wajima,1 Gaku Tachibana1 1Department of Ophthalmology, Fukui-ken Saiseikai Hospital, Fukui, 2Department of Ophthalmology, Kanazawa University Graduate School of Medical Science, Kanazawa, Japan Purpose: The purpose of this study was to clarify differences between highly myopic and non-myopic primary open-angle glaucoma (POAG) patients, including normal-tension glaucoma patients.Patients and methods: A total of 269 POAG patients were divided into two groups: patients with ≥26.5 mm of axial length (highly myopic group) and patients with <24.0 mm of axial length (non-myopic group).Results: We analyzed 53 highly myopic and 93 non-myopic POAG patients. Age at first visit of the highly myopic group was significantly less than that of the non-myopic group (P<0.0001). Baseline intraocular pressures (IOPs) showed no significant differences. Follow-up IOPs of the non-myopic group were significantly lower than those of the highly myopic group (P=0.0009). According to the mean deviation definition of progression, the cumulative probability of non-progression of visual field (VF) loss was significantly greater in the highly myopic group (10-year survival rate, 73.7%±6.8%) than in the non-myopic group (10-year survival rate, 46.3%±5.8%; log-rank test, P=0.0142). The occurrence of disk hemorrhage (DH) in the non-myopic group (1.60±3.04) was significantly greater than that in the highly myopic group (0.93±2.13, P=0.0311). The cumulative probability of DH was significantly lower in the highly myopic group (10-year survival rate, 26.4%±5.4%) than in the non-myopic group (10-year survival rate, 47.2%±6.6%, P=0.0413).Conclusion: Highly myopic POAG is considered as a combination of myopic optic neuropathy and glaucomatous optic neuropathy (GON). If GON is predominant, it has frequent DH and more progressive VF loss. However, when the myopic optic neuropathy is predominant, it has less DH and less progressive VF loss. Keywords: myopic glaucoma, disk hemorrhage, open-angle glaucoma, visual field defect progression, high myopia